تحديد الأحماض الدهنية لزيوت السلجم والبوراج وفول الصويا المنتجة في سورية - البظ ثناء (Latakia University Journal -Biological Sciences Series, 2016)
هدف البحث إلى دراسة تركيب الأحماض الدهنية لكل من زيت (السلجم– البوراج– فول الصويا) السوري بطريقة الكروماتوغرافيا الغازية GC، و مقارنة النتائج مع دراسات عالمية لنفس الزيوت المدروسة، بغية إلقاء الضوء على كل من زيت (السلجم و البوراج) السورية، لإستخدامها كبدائل أو مزائج ذات فائدة صحية أو كعامل دوائي. بيّنت الدراسة أن أهمية الزيت تكمن في مقدار النسب المئوية للأحماض الدهنية الأحادية اللاإشباع MUFA، والأحماض الدهنية العديدة اللاإشباع PUFA، والأحماض الدهنية غير المشبعة UFA، حيث كانت أعلى قيم ال UFAفي تركيب الزيوت السورية لزيت السلجم > زيت البوراج > زيت فول الصويا، كما أظهرت مقارنة نتائج البحث أن زيت السلجم المحسن والمعالج وراثيا" بأعلى نسبة مئوية لل MUFA وزيت البوراج السوري بنسبة مئوية للMUFA أقل، أما أفضل النسب المئوية لل PUFAظهرت واضحة قي زيت البوراج السوري. The research aims to Study the fatty acids composition of each of (Rapeseed- Borage-Soya bean) Oil Syrian Gas Chromatography-invasive manner, and compare the results with global studies of the same studied oils, and shed light on both the Syrian oils(Rapeseed- Borage) to be used as substitutes or mixtures of health benefit or as a drug. the study showed that the importance of the oil lies in the amount of the percentages of unsaturated fatty acids UFA and Polyunsaturated fatty acids PUFA and Monounsaturated fatty acids MUFA, with the highest values in the UFA installation Syrian oils to Rapeseed oil < Borage oil< Soya bean oil, search results compared Rapeseed oil and improved processor and the highest percentage of genetically MUFA also showed the back of Syrian oil Borage percentage of MUFA less, but The best percentage of PUFA clear appeared in the oil Borage.